2012
DOI: 10.1371/journal.pone.0047891
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to Epstein-Barr Virus Deoxyuridine Triphosphate Nucleotidohydrolase and Deoxyribonucleotide Polymerase in a Chronic Fatigue Syndrome Subset

Abstract: BackgroundA defined diagnostic panel differentiated patients who had been diagnosed with chronic fatigue syndrome (CFS), based upon Fukuda/Carruthers criteria. This diagnostic panel identified an Epstein-Barr virus (EBV) subset of patients (6), excluding for the first time other similar “clinical” conditions such as cytomegalovirus (CMV), human herpesvirus 6 (HHV6), babesiosis, ehrlichiosis, borreliosis, Mycoplasma pneumoniae, Chlamydia pneumoniae, and adult rheumatic fever, which may be mistakenly called CFS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 37 publications
0
50
0
2
Order By: Relevance
“…(Jones and Straus 1987;Miller et al 1987). In general, individuals with aberrant (elevated) levels of EA(D) antibodies, are considered to (temporally) lack proper immunological control over endogenous latent EBV, resulting in increased viral reactivation and replication and re-expression of immunogenic early antigens, as observed in "stress" and "fatigue" cohort studies (Glaser et al 2005;Lerner et al 2012), but which are also observed in patients with certain autoimmune disorders, such as SLE and RA (Ballandraud et al 2004;Lossius et al 2012), and nasopharyngeal carcinoma (Paramita et al 2007). …”
Section: Ebv Humoral Immune Responses As Defined By Classic Serology mentioning
confidence: 99%
“…(Jones and Straus 1987;Miller et al 1987). In general, individuals with aberrant (elevated) levels of EA(D) antibodies, are considered to (temporally) lack proper immunological control over endogenous latent EBV, resulting in increased viral reactivation and replication and re-expression of immunogenic early antigens, as observed in "stress" and "fatigue" cohort studies (Glaser et al 2005;Lerner et al 2012), but which are also observed in patients with certain autoimmune disorders, such as SLE and RA (Ballandraud et al 2004;Lossius et al 2012), and nasopharyngeal carcinoma (Paramita et al 2007). …”
Section: Ebv Humoral Immune Responses As Defined By Classic Serology mentioning
confidence: 99%
“…Assays of blood in some patients indicate altered T helper (Th)1 and Th2 cytokine profiles, natural killer cell function and activation of the 2-5A synthetase/ RNase L antiviral pathway. [1][2][3] Infection has been reported with a wide range of viruses and bacteria, 4 including Epstein-Barr virus, [5][6][7][8] human herpes viruses 6 and 7, [9][10][11] enteroviruses, 7,12 cytomegalovirus 13,14 and lentiviruses, 15 as well as chlamydia, 7 mycoplasma 16 and borrelia species. 17 An association of ME/CFS with central nervous system (CNS) dysfunction is supported by imaging studies documenting cerebral hypoperfusion and increased white matter T2 signal consistent with chronic inflammation 18 in addition to regional differences in gray 19 and/ or white matter.…”
Section: Introductionmentioning
confidence: 99%
“…In answering (1), valacyclovir was used successfully mostly in combination with other therapies, and on grounds of immune dysregulation— including post-transplant patients, HIV, etc— in EBV-related cases of encephalitis/various forms of CNS infection,36 37 severe/complicated (eg, with hepatic involvement)/chronic infectious mononucleosis,38 hepatitis,39 chronic fatigue syndrome,40 hairy leukoplakia,41 hydroa vacciniforme,42 various types of LPDs (eg, Burkitt lymphoma),43 oral papulosis,44 periodontitis45 and lymphocytic myocarditis 46. For these conditions, which may coexist, other antiherpetics have also been used.…”
Section: Discussionmentioning
confidence: 99%